Changes in landscape patterns and associated forest succession on the western slope of the Rocky Mountains, Colorado - Manier, Daniel J., author; Lavin, Richard D., advisor; Dean, Denis J., committee member; Laituri, Melinda J., committee member; Smith, Frederick W., committee member (Colorado State University. Libraries, 2000)
I address the prediction that fire suppression has resulted in a decline in the presence of aspen (Populus tremuloides Michaux) on the landscape. Repeat photography and size-age distribution analyses are used to assess changes in major vegetation types (coniferous forest, aspen forest, rangelands) on the western slope of the Rocky Mountains, Colorado, U.S.A. The photographs span a period of 80 to 110 years, thus representing a century of change since the large mining-related disturbances associated with European expansion and the subsequent suppression of wildfires in the region. Photos are compared using parameters representing landscape characteristics (i.e., total cover area, number of patches, mean patch size) estimated from geographic information system representations (GIS coverages). Comparisons of these documented landscapes suggest that forest cover (both aspen and coniferous) has increased across the region. Pairwise ANOVA procedures reveal significant increases in the relative total cover of aspen and conifers and a decrease in the relative coverage of rangelands. However, the number of patches and mean, relative patch size showed little significant change. High variability among sites reduces the significance of trends that are apparent in qualitative assessments and quantified trends. Analysis of size-age distributions reveal that aspen is reproducing successfully in some areas. However, my data suggest that many aspen forests are aging with limited reproductive success. In most areas, aspen populations exist within a coniferous matrix, and shade-tolerant conifer species (especially Abies lasiocarpa Nutt, and Picea engelmanii Engelm.) are abundant in the understory. Even in areas with successful aspen regeneration, successional development, which has ensued since the last major disturbance, favors reproduction by shade-tolerant species over aspen. Closed canopy aspen and conifer forests have expanded across the landscape at the expense of early serai communities. Similar data in other studies suggest that this pattern is widespread across the region. While it is apparent that the distribution of aspen on the landscape has not decreased in the last century, the structure of most of these forests is evidence of ongoing colonization by conifers. Closed canopy aspen and conifer forests have expanded across the landscape at the expense of early seral communities.
Keywords: ecology; forestry